Assessment of landslide vulnerability in Palopo City of South Sulawesi based on geological factors using a digital surface model - Witno, Witno; Nuryanti, Dewi Marwati; Yumna, Yumna; Maria, Maria; Putri, Andi Utami Batari (Brawijaya University, 2025)
Landslides are natural hazards driven by both triggering and controlling geological factors. Comprehensive assessments of landslide-prone areas and their associated volumes are essential for understanding present-day risks and informing effective mitigation strategies. This study investigates landslide vulnerability in Battang and Battang Barat Villages, Palopo City, with a focus on geological conditions, landslide extent and volume, and spatial vulnerability using Digital Surface Model (DSM) analysis. Field data were collected from 14 landslide sites through GPS mapping and aerial surveys using a DJI Mavic 2 drone. The data were processed using Agisoft Metashape Professional to generate DSM and orthomozaic imagery, while spatial analyses were performed in ArcGIS 10.5. Landslide area and volume calculations were conducted using PCI Geomatica. The analysis revealed that the average landslide-affected area is 0.30 hectares, with an estimated average volume of 5,195.58 m³. The dominant soil types include Dystric Fluvisols, Humic Ferralsols, and Ferric Acrisols, underlain by geological formations such as Lamasi Volcanic Rocks, the Latimojong Formation, and Palopo Granite. Slope gradients range from flat to steep, and land cover is primarily composed of scrub and dryland forest. The study classifies landslide vulnerability into medium and high categories, providing critical insight for site-specific hazard mitigation and land-use planning.